Repetition-Based Cooperative Broadcasting for Vehicular Ad Hoc Networks Under the Rayleigh Fading Channel - Fan Yang; Yanglong Sun; Sai Zou; Xiongbiao Luo (Applied Sciences, 2019)
In vehicular ad hoc networks (VANETs), safety applications require a reliable and delay-guaranteed broadcasting service to disseminate safety messages. However, channel fading and the high mobility of vehicles make it very challenging for a broadcasting scheme to meet the strict service demands of safety messages. On the other hand, cooperative retransmission is effective in mitigating wireless channel impairments by utilizing the broadcast nature of wireless channels. Therefore, this paper proposes a repetition-based cooperative broadcasting (RBCB) scheme for safety messages in VANETs. The proposed scheme enables the selected helper vehicles to perform the cooperative rebroadcasting along with the source vehicle during the source vehicle’s slot in order to increase the transmission reliability of safety messages and reduce rebroadcasting times. The performance of RBCB scheme is mathematically analyzed in terms of packet delivery probability and average packet delay under the Rayleigh fading channel. Moreover, extensive simulations are conducted to evaluate the performance of RBCB scheme. Both mathematical analysis and simulation results demonstrate that RBCB scheme significantly improves the packet delivery probability and decreases the average packet delay.